MODEL EKONOMI-EKOLOGI BERDASARKAN WTP PENGUNJUNG-WTA MASYARAKAT LOCAL DALAM PENGELOLAAN DESTINASI WISATA PANTAI PULISAN KABUPATEN MINAHASA UTARA - Paulus Adrian Pangemanan; Gene H. M. Kapantow; Melissa ., Tarore (AGRI-SOSIOEKONOMI, 2018)
The purpose of this research This research develops a management model of tourist destinations that integrates economic and ecological development based on the suitability of pay (WTP) of visitors with the willingness to accept (WTA) of the local community, which is supported by the role of business actors and the government. This research focuses on identifying existing economic and ecological conditions, analyzing and formulating alternative activities for economic and ecological improvement based on the willingness to pay (WTP) -willingness to accept (WTA) indicator. This research was conducted for 10 months from March to December 2018, in the tourist destination area of Pulisan Beach, North Minahasa Regency. The results of the study concluded that the willingness to pay (WTP) analysis tool to accept (WTA) can produce a choice of tourism activities and products that are desired by tourists and accepted by the local community with the support of the government and business actors. The choice of activities and products can ensure sustainable use of resources, by strengthening conservation principles. This instrument can be adapted for the management of other resources that confront economic interests, and preserve the environment and resources.